Hormone-sensitive lipase serine phosphorylation and glycerol exchange across skeletal muscle in lean and obese subjects: effect of beta-adrenergic stimulation - Jocken, Johan W E; Roepstorff, Carsten; Goossens, Gijs H; van der Baan, Paula; van Baak, Marleen; Saris, Wim H M; Kiens, Bente; Blaak, Ellen E (Diabetes (New York, N.Y.), 2008)
Increased intramuscular triacylglycerol (IMTG) storage is a characteristic of the obese insulin-resistant state. We aimed to investigate whether a blunted fasting or beta-adrenergically mediated lipolysis contributes to this increased IMTG storage in obesity. Forearm skeletal muscle lipolysis was investigated in 13 lean and 10 obese men using [(2)H(5)]glycerol combined with the measurement of arteriovenous differences before and during beta-adrenergic stimulation using the nonselective beta-agonist isoprenaline (ISO). Muscle biopsies were taken from the vastus lateralis muscle before and during ISO to investigate hormone-sensitive lipase (HSL) protein expression and serine phosphorylation. Baseline total glycerol release across the forearm was significantly blunted in obese compared with lean subjects (P = 0.045). This was accompanied by lower HSL protein expression (P = 0.004), HSL phosphorylation on PKA sites Ser(563) (P = 0.041) and Ser(659) (P = 0.09), and HSL phosphorylation on the AMPK site Ser(565) (P = 0.007), suggesting a blunted skeletal muscle lipolysis in obesity. Total forearm glycerol uptake during baseline did not differ significantly between groups, whereas higher net fatty acid uptake across the forearm was observed in the obese (P = 0.064). ISO induced an increase in total glycerol release from skeletal muscle, which was not significantly different between groups. Interestingly, this was accompanied by an increase in HSL Ser(659) phosphorylation in obese subjects during ISO compared with baseline (P = 0.008). Obesity is accompanied by impaired fasting glycerol release, lower HSL protein expression, and serine phosphorylation. It remains to be determined whether this is a primary factor or an adaptation to the obese insulin-resistant state.